Development of Web-Based Problem-Based Learning Media to Enhance Junior High School Students' Numerical Problem Solving Skills - Ilham Zhahri; Ali Asmar; Ahmad Fauzan; Yulyanti Harisman (Postgraduate, University of Mataram, 2026)
This study aimed to develop and evaluate a web-based Numerical learning media oriented toward Problem-Based Learning (PBL) to enhance junior high school students' Numerical problem-solving skills. Utilizing the Plomp research and development model, the final prototype was field-tested involving 25 eighth-grade students. The results demonstrated a classical effectiveness rate of 76%, categorizing the developed media as effective. Specifically, students exhibited exceptional proficiency in understanding the problem (93.33%) and planning a solution (88.44%). However, a significant cognitive deficit emerged in the final phase of checking the results (48.89%). It is concluded that while embedding PBL syntax into a web-based environment effectively scaffolds the forward procedural steps of Numerical problem-solving, it currently falls short in internalizing metacognitive reflection. To bridge this gap, future digital Numerical learning architectures must transcend passive information delivery by integrating interactive mechanisms, such as automated reflective prompts and dynamic feedback loops, to structurally enforce self-regulated evaluation.